Potentially lethal mouth diseases: premalignancy and oral cancer - Ficarra, Giuseppe (Henry Stewart Talks, 2017)
Epidemiology, Etiology and risk factors, Role of HPV in the pathogenesis of oropharynx and tonsillar cancer, Clinical aspects of precancerous lesions and oral cancer, PVL, Verrucous carcinoma, Diagnostic and therapeutic aspects, Prognosis of oral cancer